PROMOTING STUDENTS’ AUTONOMOUS LEARNING THROUGH ICT BASED LEARNING IN ICP: A CASE STUDY - Budianto, Langgeng (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
Promoting Information and Communication Technology (ICT) into teaching and learning is a growing area that has attracted many educators’ efforts in recent years. Based on the scope of content covered, ICT integration can happen in three different areas: curriculum, topic, and lesson. The evolution of the ICT has changed the way student or individual learns and communicates. It has created a global social network, where everyone is connected, either directly or indirectly, to each other, especially in exchanging, sharing and learning autonomously. This study attemptted to delineate how the students of International Class Program (ICP) at the Faculty of Islamic Education, handle the use of online sources. The students of ICP were selected as the informant. For eliciting information; observation and interview are used in this study. Data are collected by mean of interview guide and field notes. There are 18 students in ICP class. However for the purpose of the study, the researcher selected only three students to participate in the study. The results indicated that three respondents felt positive about using internet to perform task learning experience compared to their experiences in the regular class.